PERBANDINGAN SHALAT DAN LAKU MANEMBAH ALIRAN KEBATINAN PANGESTU DAN SUMARAH - Rosmaria Syafariah Widjayanti (Faculty of Ushuluddin and Humanities, 2015)
Adherents of Islam on Java community can be distinguished by the adherents of Islam who are santri or abangan. Muslim santri are adherents of Islam are actually based on the Koran, while the abangan Islam is a follower of Islam that unites the elements of local cultural beliefs and previous pre-Hindu, Hindu Islamic beliefs. Adherents of this syncretic Islam due to the influence and dynamism animissme ancestor’s life and under the influence of Hinduism who entered the archipelago before the arrival of Islam.